Combustion behaviors of spent mushroom substrate using TG-MS and TG-FTIR: Thermal conversion, kinetic, thermodynamic and emission analyses. (October 2018) - Huang, Jianli; Liu, Jingyong; Chen, Jiacong; Xie, Wuming; Kuo, Jiahong; Lu, Xingwen; Chang, Kenlin; Wen, Shaoting; Sun, Guang; Cai, Haiming; Buyukada, Musa; Evrendilek, Fatih
Highlights: First study on kinetic behaviors and evolved gaseous products for SMS combustion. Four iso-conversional models were adopted to calculate thermodynamic parameters. Peak of CO2 and NO2 emissions occurred at the stage of fixed carbon combustion. SO2 was released at devolatilization stage with a peak value of 334.21 °C. Abstract: The present study systematically investigated the combustion characteristics of spent mushroom substrate (SMS) using TG-MS (thermogravimetric/mass spectrometry) and TG-FTIR (thermogravimetric/Fourier transform infrared spectrometry) under five heating rates. The physicochemical characteristics and combustion index pointed to SMS as a promising biofuel for power generation. The high correlation coefficient of the fitting plots and similar activation energy calculated by various methods indicated that four suitable iso-conversional methods were used. The activation energy varied from 130.06 to 192.95 kJ/mol with a mean value of 171.49 kJ/mol using Flynn–Wall–Ozawa and decreased with the increased conversion degree. The most common emissions peaked at the range of 200–400 °C corresponding to volatile combustion stage, except for CO2, NO2 and NO. The peak CO2 emission occurred at 439.11 °C mainly due to the combustion of fixed carbon.